(untitled) (Research, Society and Development, 2021)
The study aimed to evaluate the initial growth of seedlings of six coffee cultivars in Areia-PB. The experiment was conducted between October 2019 and March 2020, in full sun in the nursery of seedlings of the Plant Ecology Laboratory, located in the Department of Phytotechnics and Environmental Sciences, in the Center of Agricultural Sciences, of the Federal University of Paraíba. The design used was in completely randomized blocks, with 6 treatments, and three repetitions, with 28 plants per plot. The cultivars were used: Bourbon; Catuaí Vermelho 144; Catuai Amarelo 62; Mundo Novo; Catucai 24/137 and Arara. The emergency percentage of seedlings, plant height, neck diameter and number of pairs of leaves were evaluated. All cultivars are promising for the region, except the Arara cultivar that has inferiority in all variables, and emergency percentage of seedlings 36.6% lower than the others. The Bourbon and New World cultivars presented better adaptation and growth superior to the other cultivars in the average height of plants at 180 days after sowing, which may indicate greater adaptation to environmental conditions, such as thermal amplitude, and insolation. In general, these results help in decision making for the choice of cultivars to be produced in the conditions of cultivation of the Paraíba Swamp and guide for future research work.